Potential of Sunda Porcupine (Hystrix javanica) Quills Extract as a Wound Healing Medicine: A Review of the Bioactive Components and Mechanisms - Yulianto; Nurcholis, Waras; Artika, I Made (Jurnal Jamu Indonesia, 2023)
Sunda porcupine (Hystrix javanica), a native species of Indonesia, is renowned for its distinctive sharp quills enveloping its body. Despite its reputation as a spiky creature, the use of porcupine quills in traditional medicine in Indonesian society, especially for toothache and stomach ulcers, shows that there are benefits as an alternative to herbal medicine that has yet to be fully explored. Even outside Indonesia, North American porcupine quills are reported to have antibiotic properties related to the free fatty acids that coat the spines. Extracts of Sunda porcupine quills have also shown interesting antibacterial activity. Several bioactive compounds have been found in Sunda porcupine quills extract, including alkaloids, flavonoids, saponins, steroids, triterpenoids, and peptides. These compounds have various health benefits, such as analgesic, anti-inflammatory, and antimicrobial. In addition, the antibacterial activity test on the extract showed strong potential against the growth of gram-positive bacteria. The activities of secondary metabolites that play a role in helping wound healing are anti-inflammatory, antioxidant, and antibacterial/antimicrobial activities. Wound healing mechanisms involve several complex interactions of various cellular and molecular processes. Recent research has revealed the great potential of extracts from Sunda porcupine quills as a wound healing medicine. Although the potential of Sunda porcupine quills extract as a wound healing medicine has attracted attention, this research still has limitations. Critical measures, such as in vivo and in vitro testing, still need to be improved, leaving gaps in information that require further research. The challenge of an in-depth understanding of the activity and mechanisms of bioactive compounds is the focus on optimizing the utilization of Indonesia's natural potential. This article reviews the bioactive components of Sunda porcupine quills extract and their mechanism as a wound healing agent.